PENGARUH INTENSITAS ASET TETAP DAN INTENSITAS PERSEDIAAN TERHADAP PENGHINDARAN PAJAK DENGAN PERTUMBUHAN PENJUALAN SEBAGAI VARIABEL MODERASI - Kevin Muhammad Pransilva Nasution; Susi Dwi Mulyani (Prosiding Seminar Nasional Pakar, 2020)
The purpose of this study was to examine the effect of fixed asset intensity and inventory intensity on tax avoidance with sales growth as moderation variable in consumer good companies listed on the Indonesia Stock Exchange during the period of 2014-2018. This study uses profitability and leverage as control variable on relationship between independent variables and dependent variable. This study uses purposive sampling method to sort data. The sample being researched are 23 companies with 5 years observation. Data processing is done by using SPSS. The hypothesis are tested using multiple linear regression. The result showed that there is significant negative influence between Fixed Asset Intensity with tax avoidance, there is  significant negative influence between inventory intensity  with tax avoidance. In addition, sales growth did not effect the influence between fixed asset intensity tax avoidance, and unable to moderate the influence between inventory intensity with tax avoidance.